THE ASSOCIATION OF DIABETES DURATION WITH THE SEVERITY OF DIABETIC RETINOPATHY - Intan Lamy Manao; Hesti Triwahyu Hutami; Fifin Luthfia Rahmi; Arnila Novitasari Saubig (Jurnal Kedokteran Diponegoro)
Background: The prevalence of diabetic patients is increasing over the years. It will increase the incidence of microvascular complications due to prolonged hyperglycemia in diabetic patient. Diabetic retinopathy is one of microvascular complication which is one of the leading causes of blindness in the world. Prolonged hyperglycemia in diabetic patient cause toxicity to the retina which cause nerve and vascular damage and death to the retina. In this study was analyzed the association of diabetes duration with the severity of diabetic retinopathy associated with many cases of delay in diagnosing diabetes recently